Experiencing affective music in eyes-closed and eyes-open states: an electroencephalography study - Chang, Yun-Hsuan; Lee, You-Yun; Liang, Keng-Chen; Chen, I-Ping; Tsai, Chen-Gia; Hsieh, Shulan (Frontiers in Psychology, 2015)
In real life, listening to music may be associated with an eyes-closed or eyes-open state. The effect of eye state on listeners' reaction to music has attracted some attention, but its influence on brain activity has not been fully investigated. The present study aimed to evaluate the electroencephalographic (EEG) markers for the emotional valence of music in different eye states. Thirty participants listened to musical excerpts with different emotional content in the eyes-closed and eyes-open states. The results showed that participants rated the music as more pleasant or with more positive valence under an eyes-open state. In addition, we found that the alpha asymmetry indices calculated on the parietal and temporal sites reflected emotion valence in the eyes-closed and eyes-open states, respectively. The theta power in the frontal area significantly increased while listening to emotional-positive music compared to emotional-negative music under the eyes-closed condition. These effects of eye states on EEG markers are discussed in terms of brain mechanisms underlying attention and emotion.